The Role of Expectations and Endogenous Opioids in Mindfulness-Based Relief of Experimentally Induced Acute Pain. Issue 6 (July 2021) - Case, Laura; Adler-Neal, Adrienne L.; Wells, Rebecca E.; Zeidan, Fadel
ABSTRACT: Objective: Expectations contribute to cognitive pain modulation through opioidergically mediated descending inhibition. Mindfulness meditation reduces pain independent of endogenous opioids, engaging unique corticothalamocortical mechanisms. However, it remains unknown whether expectations for pain relief predict mindfulness-induced analgesia and if these expectations are modified by endogenous opioids. Methods: In this secondary analysis of previously published work, 78 pain-free participants (mean age, 27 ± 7 years; 50% women) were randomized to a four-session mindfulness meditation or book listening regimen. Expectations for intervention-induced pain relief were assessed before and after each intervention. Pain ratings were examined after meditation or rest (control group) during noxious heat (49°C) and intravenous administration of saline placebo or the opioid antagonist naloxone (0.15 mg/kg bolus + 0.1 mg kg −1 h −1 infusion. Results: Mindfulness significantly lowered pain during saline and naloxone infusion. Higher expected pain relief from mindfulness predicted lower pain intensity ( r (40) = −0.41, p = .009). The relationship between meditation-related expectations and pain intensity reductions was exhibited during naloxone ( r (20) = −0.76, p < .001) but not saline ( r (20) = −0.22, p = .36). Expectations for book listening–based analgesia did not significantly predict pain changes during saline ( r (20) = −0.37, p = .11) or naloxone ( r (18) = 0.26, p = .30) in the control group. Conclusions: These novel findings demonstrate a significant role for expectations in mindfulness-based pain relief. However, this role was minimal during saline and stronger during opioid blockade, despite similar pain reductions. This supports growing evidence that mindfulness engages multiple mechanisms to reduce pain, suggesting that mindfulness might be an effective pain-reducing technique even for individuals with low expectations for pain relief.